The Effect of Rainfall Change on the Vegetation Cover Map for Jordan 2019-2021 Using Geospatial Techniques - Abu rukaba, Rasha Ahmad (Journal of natural sciences, life and applied sciences, 2022)
The Remote Sensing technic and Geographic Information System became a vital tool for monitoring and extracting data of natural resources on the earth’s surface while climate change became one of the natural phenomena considered a hot spot for investigation. Based on the international earth circulation models, the middle east areas will notify increasing the greenhouse gases concentration in the atmosphere, decreasing in precipitation, and increase air temperature which lead to an increase of latent heat vaporization. Jordan already suffering from the amount of renewable groundwater resources and decreasing in agricultural production in the last period, based on the data of the last rainy season 2020-2021 compared with 2019-2020, the geospatial technic has been adopted in order to have a full analysis of the impact rainfall distribution change of vegetation cover maps for the years 2019-2020, based on the Normalized Difference Vegetation Index and cartographic criteria a digital map where produced that reflect the true reality of vegetation cover in terms of density, spatial distribution, areal distribution, and precipitation in terms of quantity and variety. The results showed that there is a decline of the rainy season 2020-2021 from the rainy season 2019-2020, through the decline of the spatial distribution of vegetation cover for the season 2019-2020 from a strip extending from north to south in the western side of the Kingdom, to its dominant expected area in the northwestern side of the season 2020 –2021, furthermore a clear decline in area of vegetation cover where its value is greater than the average (deviation from the average), the area of surface water decreased by (43%), barren lands increased by (1.2%), lands with medium-intensity vegetation decreased by (17%), and lands with cover increased by )17%(. Where the area of high value of NDVI has increased by (12%) high, and the NDVI has decreased from (0.74 to 0.73). Thus, it could be concluded that the spatial distribution, spatial distribution and the intensity of the NDVI are affected by the characteristics of rain with a positive relationship. this study recommends the necessity of adopt geospatial techniques as a vital tool to identify the changes of vegetation cover, producing and updating vegetation cover maps and the impact of climatic characteristics on their spatial distribution and spatial spread.